2011
DOI: 10.1117/12.876738
|View full text |Cite
|
Sign up to set email alerts
|

Large scale micropatterning of multi-walled carbon nanotube/polydimethylsiloxane nanocomposite polymer on highly flexible 12×24 inch substrates

Abstract: We present the large scale micro-pattering of an electrically conducting multiwalled carbon nanotube (MWCNT) polydimethylsiloxane (PDMS) nanocomposite polymer prepared by high frequency (42 kHz) ultrasonic agitation of MWCNTs in the PDMS polymer matrix. Large scale micropatterning of the MWCNT-PDMS nanocomposite is achieved via soft lithography employing a 12" x 24" poly-methyl methacrylate (PMMA, commercially known as Plexiglass) micromold. The process has a 20µm.minimum feature size. The PMMA micromold is fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Recently, there have been researches on finding the optimum solvents to disperse CNTs into specific polymer matrices such as PDMS . Interestingly, Liu and Choi reported that although some of the organic solvents worked well for the dissolution of PDMS and the dispersion of MWCNTs, separately, they might not work when they were used for dispersing the MWCNTs into the PDMS solution .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been researches on finding the optimum solvents to disperse CNTs into specific polymer matrices such as PDMS . Interestingly, Liu and Choi reported that although some of the organic solvents worked well for the dissolution of PDMS and the dispersion of MWCNTs, separately, they might not work when they were used for dispersing the MWCNTs into the PDMS solution .…”
Section: Introductionmentioning
confidence: 99%
“…Significant research has been conducted on the micro-patterning of flexible materials to form sensing purposes. One of them has been explained by Khosla et al in regards to the fabrication of arrayed-sensors on flexible 12 × 24 inch substrates from MWCNTs-PDMS nanocomposites [68]. The difference of this methodology from that of the first one explained in this section lies in the use of micro-contact patterning which helps in differentiating the intensity of the induced-strain corresponding to different locations.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of the individual electrodes in the array with similar dimensions were also done to show that the resistances of these electrodes were around 9.93 Ωm. Figure 2 shows the schematic diagram of the individual steps of the fabrication process [68].…”
Section: Methodsmentioning
confidence: 99%
“…A common way to fabricate a conductive elastomer is by mixing flexible material and conductive material, and then curing the composites by baking. The most commonly used flexible material for conductive elastomer fabrication is polydimethylsiloxane (PDMS) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%